2022
DOI: 10.1161/hypertensionaha.121.17704
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Arterial Stiffness in Association With Aircraft Noise Exposure:Long-Term Observation and Potential Effect of COVID-19 Lockdown

Abstract: In a cross-sectional analysis of a case-control study in 2015, we revealed the association between increased arterial stiffness (pulse wave velocity) and aircraft noise exposure. In June 2020, we evaluated the long-term effects, and the impact of a sudden decline in noise exposure during the coronavirus disease 2019 (COVID-19) lockdown, on blood pressure and pulse wave velocity, comparing 74 participants exposed to long-term day-evening-night aircraft noise level > 60 dB and 75 unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…This, in turn, favors the development of cardiovascular risk factors, such as arterial hypertension and accelerates atherosclerotic disease progression, contributing to the manifestation of cardiovascular disease. 7 In good agreement with the nonauditory noise reaction proposed by Babisch, Wojciechowska et al 2 demonstrate the interplay between noise annoyance and arterial disease progression, as decreases in blood pressure and pulse wave velocity were accompanied by decreased noise annoyance in exposed subjects, as a result of the COVID-19 lockdown–induced short-term reduction in noise levels. Conversely, the cumulative and long-lasting effect of chronic noise exposure on arterial disease progression over time is represented by an increased prevalence of hypertension in exposed subjects.…”
supporting
confidence: 80%
“…This, in turn, favors the development of cardiovascular risk factors, such as arterial hypertension and accelerates atherosclerotic disease progression, contributing to the manifestation of cardiovascular disease. 7 In good agreement with the nonauditory noise reaction proposed by Babisch, Wojciechowska et al 2 demonstrate the interplay between noise annoyance and arterial disease progression, as decreases in blood pressure and pulse wave velocity were accompanied by decreased noise annoyance in exposed subjects, as a result of the COVID-19 lockdown–induced short-term reduction in noise levels. Conversely, the cumulative and long-lasting effect of chronic noise exposure on arterial disease progression over time is represented by an increased prevalence of hypertension in exposed subjects.…”
supporting
confidence: 80%
“…Wojciechowska et al . 39 reported that aircraft noise reduction during the lockdown was associated with a decrease in BP. This suggests that a reduction in daily social stress might lower BP, even during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the causal association between diesel exhaust exposure and dysfunction of immune response was confirmed, and the usefulness of metabolomic analysis was shown (Cheng et al, 2022). The multiple adverse impacts on the health of noise exposure were reported in plenty of studies (Essers et al, 2022;Wojciechowska et al, 2022), and its associations with immune response were also indicated. Consistently, in this study, a variety of biological processes associated with the DMs-NE were shown.…”
Section: Discussionmentioning
confidence: 99%